Exploring male batterer's experiences in a batterer education program: implications to educational practice - Godbersen, Jill Schafer (1999)
Startling statistics indicate that one in three women will experience at least one physical assault by a partner during adulthood. Violence and abuse between partners have real and significant effects on individuals, families, communities, and society. Despite research on domestic abuse intervention programs, inconclusive results exist regarding how male batterers stop their abuse against their partners;The general purpose of this study was to explore Mezirow's transformative learning theory as a possible explanation for the learning and change batterers experience in stopping their abuse. Secondary purposes were to utilize victim input regarding the batterer's educational experience, and to track and examine the experiences of male batterers in a batterer education program;Qualitative inquiry was used in this phenomenological study. Seven male batterers and one female victim were studied at the Boys & Girls Home & Family Services Agency in Sioux City, Iowa. Batterers were interviewed three times each over a four month period during their educational program. Data was extracted from interviews, observations, and documents;The data from this study were analyzed using the constant comparative method to inductively discover theory from data. Results from data analysis found six main themes from the batterer narratives: patriarchal belief systems, jealousy and control, verbal and physical abuse, blaming others, learning new tools, and making changes;Conclusions from the study were as follows: (1) Becoming a non-batterer is a slow, gradual process, (2) Critical reflection needs to occur if batterers are going to make serious, life-long changes in their behavior, (3) Information learned in the BEP did assist the batterers in changing their abusive behaviors, (4) The BEP served as a catalyst in assisting the batterers to see alternative world views regarding women, relationships, and violence, and (5) Perspective transformation did occur to different degrees in each batterer